A Functional BCI Model by the P2731 working group: Physiology. Issue 3 (3rd July 2021) - Hossaini, Ali; Valeriani, Davide; Nam, Chang S.; Ferrante, Raffaele; Mahmud, Mufti
ABSTRACT: The development of Brain–Computer Interfaces (BCIs) requires specialists in various fields, including engineering, computer science, medicine and neuroscience. Each of these disciplines possesses a specific and sometimes differing terminology, which creates obstacles to mutual understanding and research collaboration. The IEEE P2731 working group aims to improve communication among BCI researchers by developing a functional model and standard glossary that can be used in all relevant fields. This article describes the anatomical regions of the brain and physiological processes commonly used by BCI applications. It serves as an introduction to neurophysiology for engineers and other non-specialists, and it offers background to articles on the IEEE P2731 Functional Model and Glossary available elsewhere in this special issue.